Afrint I-III - Andersson Djurfeldt, Agnes (Lund University, 2018)
The project aims to analyse broad based agricultural growth from a gender perspective, and to situate these processes locally, against the backdrop of national agricultural policies and broader demographic, socio-economic changes. The objective of the study is to assess under what social and institutional conditions pro-poor agricultural growth entrenches or redresses gender based differences in access to agrarian resources, and what consequences this has for linkages to the nonfarm sector. This inquiry will be approached from the village, household and individual levels through three key research questions:

How can the consequences of gender differentiated access to productive and institutional resources during processes of broad based agricultural growth be understood?

How can linkages between agriculture and the nonfarm sector be analysed from a gender perspective, given that nonfarm income may be important in alleviating inferior access to agrarian resources among women in particular?

What village level characteristics are relevant to understanding the dynamics of broad based agricultural growth and nonfarm/farm interaction from a gender perspective?

Purpose:

The Afrint project which has been running since 2002 is an interdisciplinary, comparative project looking initially at the possibilities for an Asian style Green Revolution in nine countries in Sub-Saharan Africa on the basis of household level data for around 4000 smallholder farms.

The second phase, Afrint II, was launched in 2008 and aimed to trace patterns of change among these households given the growing policy interest in smallholder based agrarian development in both national, regional and international circles. Since 2010, a downsized Afrint III was launched covering the original sample in six countries – Ghana, Kenya, Malawi. Mozambique, Tanzania and Zambia - in which the scope has been broadened to include linkages between farm and non farm sources of livelihoods as well as gendered patterns of access to income both within and outside agriculture.

Longitudinal dataset that contains panel data for smallholders interviewed in 2002, 2007 and 2012/2015. Cross-sections consist of 2325, 2473 and 2544 households, respectively. The full panel contains 1566 households. Interviews have been carried out by the self-identified household head.

Studien har följt 1566 småbrukarhushåll i sex afrikanska länder sedan 2002, syftet har varit att förstå hur jordbruket har utvecklats över de senaste femton åren, givet stora investeringar i jordbruket.

Syfte:

Ursprungssyftet har varit att undersöka förutsättningarna för jordbruksintensifiering i Afrika söder om Sahara. Detta har sedan vidgats till att försöka kartlägga och förstå kopplingen mellan agrara och icke-agrara försörjningsmöjligheter i synnerhet med fokus på skillnader mellan män och kvinnor.

Longitudinellt dataset som innehåller data för en panel av småbrukare intervjuade 2002, 2007 respektive 2012/2015. Tvärsnitten består av 2325, 2473 respektive 2544 hushåll. Panelen består av 1566 hushåll. Intervjuer har genomförts med hushållsöverhuvudet.
Afrint I-III
Keywords: ASSETS; TILLGÅNGAR; SEX; KÖN; RURAL DEVELOPMENT; LANDSBYGDSUTVECKLING; Africa; Afrika; structural transformation; strukturell omvandling; commercialization; kommersialisering; non-farm; non-farm; smallholder; småjordbruk; diversification; diversifiering; ECONOMICS; EKONOMI; HOUSING AND LAND USE; BOSTÄDER OCH MARKANVÄNDNING; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap